Bigfoot - Peabody, Erin (Peabody, Erin. Behind the legend., 2017)
"This new nonfiction series looks at creatures and monsters throughout history and analyzes them through a scientific, mythbusting lens, debating whether or not the sightings and evidence provided are adequate proof of their existence. In Bigfoot, readerslearn about all the sightings and "proof" of it, from the famous photograph and video to footprints and other evidence. It also discusses additional history about the monster, such as how Bigfoot became a major figure in popular culture, and how other versions of the creature (such as the Yeti) have been seen around the world. Complete with engaging anecdotes, interesting sidebars, and fantastic illustrations, kids won't want to put this book down!"--